2013
DOI: 10.1016/j.jctb.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Substitution and χ -boundedness

Abstract: A class G of graphs is said to be χ-bounded if there is a function f : N → R such that for all G ∈ G and all induced subgraphs H of G, χ(H) ≤ f (ω(H)). In this paper, we show that if G is a χ-bounded class, then so is the closure of G under any one of the following three operations: substitution, gluing along a clique, and gluing along a bounded number of vertices. Furthermore, if G is χ-bounded by a polynomial (respectively: exponential) function, then the closure of G under substitution is also χ-bounded by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(77 citation statements)
references
References 22 publications
(35 reference statements)
0
76
0
1
Order By: Relevance
“…As observed by Penev, for large values of k , a stronger result was implicitly proved in . Theorem If a class of graphs is χ‐bounded by ffalse(xfalse)=xA, then the closure of the class under substitution is χ‐bounded by gfalse(xfalse)=x3A+11.…”
Section: A Property Closed Under Substitutionsmentioning
confidence: 82%
See 2 more Smart Citations
“…As observed by Penev, for large values of k , a stronger result was implicitly proved in . Theorem If a class of graphs is χ‐bounded by ffalse(xfalse)=xA, then the closure of the class under substitution is χ‐bounded by gfalse(xfalse)=x3A+11.…”
Section: A Property Closed Under Substitutionsmentioning
confidence: 82%
“…Also gluing along a proper 2‐cutset preserves χ‐boundedness as shown in . Theorem If a class of graphs is χ‐bounded, then its closure under the operation of gluing along a proper 2‐cutset is χ‐bounded.…”
Section: Operations and Properties Preserved By Themmentioning
confidence: 97%
See 1 more Smart Citation
“…This theorem was improved by Chudnovsky, Penev, Scott, and Trotignon [2] who showed that the condition χ(G) > max{c+2k 2 , 2k 2 +k} is sufficient. The proof from [2] relies on an ad hoc induction hypothesis, which roughly states that upper bounds on the chromatic number are preserved under gluing along a fixed number of vertices.…”
Section: Introductionmentioning
confidence: 99%
“…The proof from [2] relies on an ad hoc induction hypothesis, which roughly states that upper bounds on the chromatic number are preserved under gluing along a fixed number of vertices.…”
Section: Introductionmentioning
confidence: 99%